2004
DOI: 10.1055/s-2004-827204
|View full text |Cite
|
Sign up to set email alerts
|

α-Spinasterol Isolated from the Root ofPhytolacca americanaand its Pharmacological Property on Diabetic Nephropathy

Abstract: Based on an inhibitory activity-guided fractionation for the high glucose-induced proliferation of glomerular mesangial cells (GMCs), chloroform extracts of the roots of Phytolacca americana were found to contain alpha-spinasterol (C (29)H (48)O), a delta (7)-sterol. This phytosterol proved to be a potent inhibitor (IC (50) = 3.9 x 10 (-12) g/mL, 9.5 pmol/L) of glomerular mesangial cell proliferation caused by high-ambient glucose (5.6 mM vs. 25 mM), and its inhibitory potency was about 1,000 times higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…The effect of spinasterol on reducing plasma and liver cholesterol levels has been recognized for many years (22). The antitumorigenic potential of spinasterol also was demonstrated previously (23), and more recently, spinasterol was found to have considerable therapeutic potential in modulating the development and/or progression of diabetic nephropathy (24). On the other hand, dihydrospinasterol showed a potent inhibitory effect on the Epstein-Barr virus early antigen (25), whereas its glucoside exhibited anticarcinogenic and cytotoxic potential (26).…”
Section: Resultsmentioning
confidence: 94%
“…The effect of spinasterol on reducing plasma and liver cholesterol levels has been recognized for many years (22). The antitumorigenic potential of spinasterol also was demonstrated previously (23), and more recently, spinasterol was found to have considerable therapeutic potential in modulating the development and/or progression of diabetic nephropathy (24). On the other hand, dihydrospinasterol showed a potent inhibitory effect on the Epstein-Barr virus early antigen (25), whereas its glucoside exhibited anticarcinogenic and cytotoxic potential (26).…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, former research has reported the ability of α‐spinasterol to decrease the incidence of skin tumors without co‐carcinogen or co‐tumor promoter activities . Also, α‐spinasterol was reported to be a potent inhibitor of glomerular mesenglial cell proliferation caused by high ambient glucose in mouse model of induced diabetic nephropathy …”
Section: Discussionmentioning
confidence: 99%
“…-spinasterol, 22, 23-dihydro--spinasterol (Janson et al 2009, Elvia et al 2010, Jeong et al 2004, Ling et al 2010, and -spinasteryl--D-glucoside (Kojima et al 1990, Gafur et al 1997 were reported from various plant sources. But 22, 23-dihydro-spinasteryl--D-glucoside was not reported earlier.…”
Section: 23-dihydro--spinasteryl--d-glucosidementioning
confidence: 99%